A survey of the knowledge of the military and civilian medical practitioners in the Royal Medical Service in the Kingdom of Bahrain with regards to the clinical application of hyperbaric oxygen therapy - Abdulaal, A. A. M. (Adel) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScMedSc)--Stellenbosch University, 2012.